2020
DOI: 10.1080/00325481.2020.1752010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fetal loss in severe acute pancreatitis during pregnancy: a 5-year single-tertiary-center retrospective analysis

Abstract: Objective: To determine the factors that predict fetal loss in patients with severe acute pancreatitis. Methods: A total of 96,132 cases including 215 patients with acute pancreatitis were evaluated, and 83 cases with severe acute pancreatitis were included in the study. Clinical data and maternal complications were analyzed. Results: The incidence of acute pancreatitis during pregnancy was 2.24%, of which 38.6%had severe acute pancreatitis. The maternal mortality and fetal mortality were 3.6% and 32.5%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…As reported in our previous research, the mean gestation week for the fetal death group was 32.7 ± 4.7 weeks, while the fetal survival group was 36.4 ± 2.2 weeks ( 25 ). Other studies also reported that earlier gestation week was related to higher fetal mortality ( 4 , 17 , 26 ). For example, Tang et al reported that six patients suffered fetal deaths in the first or second trimester ( 4 ), and Xu et al reported that five patients had fetal deaths in the first or second trimester ( 13 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As reported in our previous research, the mean gestation week for the fetal death group was 32.7 ± 4.7 weeks, while the fetal survival group was 36.4 ± 2.2 weeks ( 25 ). Other studies also reported that earlier gestation week was related to higher fetal mortality ( 4 , 17 , 26 ). For example, Tang et al reported that six patients suffered fetal deaths in the first or second trimester ( 4 ), and Xu et al reported that five patients had fetal deaths in the first or second trimester ( 13 ).…”
Section: Discussionmentioning
confidence: 82%
“…Second, as one of the largest acute pancreatitis transfer centers in China, the majority of patients were diagnosed with SAP (47.78%) and HTG-APIP (64.4%). Tang et al and Yang et al report that HTG is a risk factor for fetal death in APIP ( 8 , 26 ). Compared with other etiologies, HTG-APIP was more prevalent in severe AP cases, with more complications, and poorer prognosis ( 7 , 13 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this nested case-control study, AMA women with fetal loss at 14 weeks of gestation or later were enrolled as the case group; fetal loss included induced labor due to fetal abnormality, spontaneous or artificial abortion, and stillbirth [9]. The fetal abnormalities included congenital abnormalities and chromosomal abnormalities, such as anencephalus, single atrium, single ventricle, gastroschisis, thanatophoric dwarfism, trisomies, and monosomy X [11].…”
Section: Subjectsmentioning
confidence: 99%
“…AMA has been associated with adverse pregnancy outcomes, including spontaneous abortion, fetal chromosomal and congenital abnormalities, spontaneous late preterm delivery, and stillbirth [6][7][8]. Abortion, stillbirth, or induced labor can lead to fetal loss [9]. Some studies have shown that the risk of adverse perinatal outcomes is elevated with increasing maternal age [10].…”
Section: Introductionmentioning
confidence: 99%
“…SAP in pregnancy (SAPIP) is hazardous to the health of pregnant women, andthe maternal mortality rate can be as high as about 20-40% [1,6]. The fetus of SAPIP is even prone to intrauterine distress and death [7][8][9].…”
Section: Introductionmentioning
confidence: 99%